The Effect of Using English Video on Students' Vocabulary Mastery at SMP PSKD 6 Depok - Grathia, Ellyah (JET (Journal of English Teaching), 2017)
ABSTRACTThe main objective of this research is to find out whether or not there is any significant effect of using English video on students‟ vocabulary mastery at SMP PSKD 6 Depok. This study is an experimental research that consists of two classes, the experimental class and control class. The research was done on April 2016 until May 2016. The subject of the research was eighth graders‟ students VIII B and VIII C at SMP PSKD 6 Depok. The consisted of 20 students. The instruments of the test were pre-test and post-test. The improvement of the eighth graders‟ vocabulary scores can be seen from the results of the pre-test and post-test. The mean scores of the experimental class in the pre-test was 57.35 points. While the mean scores of the control class in the pre-test was 52.60 points. The average score of the experimental class in the post-test was 71.40 points. While the average scores of the control class in the post-test was 60.00 points. The data obtained clarified that there was a significant effect of using English video on students‟ vocabulary mastery. By using English video, students‟ in experimental class ranged of the average score from 57.35 points until 71.40 points. The hypotheses tested in this research showed that there was a significant effect of English video. The value of Sig. of equality variances (0.760) was higher than Sig. α (0.05). This finding indicates that the sample data were taken from homogeneous population variances. Based on the result of the research, it was concluded that the use of English video on students‟ vocabulary mastery at SMP PSKD 6 Depok. The writer suggests using English video is one of the effective technique to improve students‟ vocabulary, especially in teaching English in eighth graders. Keyword: experimental research, English video, vocabulary